2009
DOI: 10.1021/am800199u
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Epoxy Coatings

Abstract: The design, formulation, and characterization of new epoxy coatings with built-in chemical and threshold temperature sensors are reported. The materials were prepared by dissolving a chromogenic, fluorescent oligo(p-phenylenevinylene) dye into a cross-linked epoxy resin by reacting monomer/cross-linker/dye mixtures at 180-200 degrees C and quenching the cured polymer to below its glass transition temperature (T(g)). Subjecting these kinetically trapped, thermodynamically unstable molecularly mixed epoxy/dye bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…The approach exploits the excimer-forming properties of chromophores such as cyano-substituted oligo(phenylene vinylene)s [7][8][9][10][11][12] (cyano-OPVs, Figure 1) and further relies on the stimulus-driven self-assembly or dispersion of nano-scale aggregates of these sensor dyes in a range of host polymers. We have shown that this general concept of stimulus-triggered dye (dis)assembly in polymer matrices allows for the design of a broad range of sensor materials, which are useful for the detection of temperature history, [13][14][15][16][17] exposure to chemicals, [18,19] and mechanical deformation, [20][21][22][23][24] as well as more complex combinations of stimuli, such as seen in shape-memory materials. [25] Others have adapted the concept and extended it to a range of dyes including cyano containing poly(phenylene ethynylenes), [26] perylenes, [27] CdS nanoparticles, [28] and bis(benzoxazolyl)stilbenes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The approach exploits the excimer-forming properties of chromophores such as cyano-substituted oligo(phenylene vinylene)s [7][8][9][10][11][12] (cyano-OPVs, Figure 1) and further relies on the stimulus-driven self-assembly or dispersion of nano-scale aggregates of these sensor dyes in a range of host polymers. We have shown that this general concept of stimulus-triggered dye (dis)assembly in polymer matrices allows for the design of a broad range of sensor materials, which are useful for the detection of temperature history, [13][14][15][16][17] exposure to chemicals, [18,19] and mechanical deformation, [20][21][22][23][24] as well as more complex combinations of stimuli, such as seen in shape-memory materials. [25] Others have adapted the concept and extended it to a range of dyes including cyano containing poly(phenylene ethynylenes), [26] perylenes, [27] CdS nanoparticles, [28] and bis(benzoxazolyl)stilbenes.…”
Section: Introductionmentioning
confidence: 99%
“…[29] The temperature and humidity sensors based on such polymer/dye blends operate by kinetically trapping a thermodynamically unstable molecular mixture of the components by rapidly cooling a hot (and at this temperature miscible) mixture below its glass transition temperature (T g ). [13,19] If the material is subsequently heated above T g , the system becomes sufficiently mobile to equilibrate, resulting in aggregation of the dye molecules and the formation of excimers. This approach yields timetemperature indicating materials that exhibit a pronounced fluorescence color change, whose kinetics follow a predictable, Arrhenius-type behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the study did also not involve well-defined supramolecular assemblies, the results paved the way for subsequent work on mechanochromic polymers comprising assemblies of aggregachromic, excimer-forming cyano-substituted oligo(p-phenylene vinylene)s (cyano-OPVs, Figures 2-4). [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Scanning confocal microscopy images of blend films of ultra-high-molecular-weight polyethylene and 10 -4 % w/w EHO-OPPE (Figure 1). a) As prepared film.…”
Section: π-π Interactionsmentioning
confidence: 99%
“…Initial kinetic experiments reflect a behavior that mirrors the response of the thermally triggered systems discussed above: as expected, the switching from monomer to excimer emission is much faster for samples exposed to higher humidity levels and the color changes appear again to be well described by single exponential functions. The framework was recently also adapted to create epoxy-based, thermosetting epoxy resins, as examples for thermosetting polymers with integrated sensing capabilities [74]. Such resins are widely used for decorative, protective, and/or functional coatings [75].…”
Section: Chemical Sensing With Excimer-forming Dyesmentioning
confidence: 99%